2017
DOI: 10.15294/biosaintifika.v9i3.12382
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Chromosomal Aberrations and Micronuclei in Medical Workers Chronically Exposed to Low Dose Ionizing Radiation

Abstract: Medical workers representing the group is the most consistently are exposed to low doses of ionizing radiation, prolonged low-level ionizing radiation can induce chromosomal aberrations (CAs). This study would evaluate the cytogenetic effect using the CAs based on dicentric, and cytokinesis-blocked micronucleus (CBMN) assay on hospital workers. The exposed group dividedto Interventional and Diagnostic groups then compared to non exposed group. The accumulated absorbed doses calculated for the radiation workers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 17 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…One cytogenetic technique that is easy and simple to quantify the damage caused by radiation exposure in cultured human lymphocytes is MN (Fenecht et al, 1990). MN with the cytokinesis-block micronucleus (CBMN) assay is a superior, validated, standard technique for assessing radiation exposure in individuals exposed to ionizing radiation and determining radiosensitivity of cancer susceptibility in vitro (Lusiyanti et al, 2016;Lusiyanti et al, 2017). Micronuclei form during the cell's mitotic division and contain whole chromosomal or acentric chromosomal fragments that are not incorporated into the cell nucleus (Özdal et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…One cytogenetic technique that is easy and simple to quantify the damage caused by radiation exposure in cultured human lymphocytes is MN (Fenecht et al, 1990). MN with the cytokinesis-block micronucleus (CBMN) assay is a superior, validated, standard technique for assessing radiation exposure in individuals exposed to ionizing radiation and determining radiosensitivity of cancer susceptibility in vitro (Lusiyanti et al, 2016;Lusiyanti et al, 2017). Micronuclei form during the cell's mitotic division and contain whole chromosomal or acentric chromosomal fragments that are not incorporated into the cell nucleus (Özdal et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the micronucleus (MN) assay that reflects chromosomal injury is useful as a biomarker for monitoring environmental effects on the genetic material in human cells (Perumal et al, 2015). The two methods have also been used in previous research Yanti Lusiyanti et al / Biosaintifika (1) (2021): 9-15 to evaluate the cytogenetic impact of chronically exposed to low dose ionizing radiation hospital medical workers (Lusiyanti, et al, 2017). The previous study reported that cancer patients indicated different sensitivities and showed increased chromosomal instability compared with healthy individuals (Garaj-vrhovac & Kopjar, 2018).…”
Section: Introductionmentioning
confidence: 99%